Techniques of Technical and Tactical Training on the Use of Innovative Technologies for Hearing Handball Players - Ibragimov Alisher Karomatovich; Ravshanov Amirali Alimardon o’g’li (Research Parks Publishing LLC, 2022)
to develop information technology for technical and tactical training of skilled handball players with hearing impairments. Application of information technology had an impact on the competitive result.